Advances in social simulation : Proceedings of the 9th conference of the European social simulation association - Koloch, Grzegorz; Kaminski, Bogumil (Advances in Intelligent Systems and Computing, 2014)
This book is the conference proceedings of ESSA 2013, the 9th Conference of the European Social Simulation Association. ESSA conferences constitute annual events which serve as an international platform for the exchange of ideas and discussion of cutting-edge research in the field of social simulations, both from the theoretical as well as applied perspective. This book consists of 33 articles, which are divided into four themes: Methods for the development of simulation models, Applications of agent-based modeling, Adaptive behavior, social interactions and global environmental change and Using qualitative data to inform behavioral rules. We are convinced that this book will serve interested readers as a useful compendium which presents in a nutshell the most recent advances at the frontiers of social simulation research.